2007
DOI: 10.1111/j.1471-4159.2007.05017.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of local perfusion of DAMGO on extracellular GABA and glutamate concentrations in the rostral ventromedial medulla

Abstract: Electrophysiological data suggest an involvement of rostral ventromedial medulla (RVM) GABA and glutamate (GLU) neurons in morphine analgesia. Direct evidence that extracellular concentrations of GABA or GLU are altered in response to mu opioid receptor (MOP‐R) activation is, however, lacking. We used in vivo microdialysis to investigate this issue. Basal GABA overflow increased in response to intra‐RVM perfusion of KCl (60 mmol/L). Reverse microdialysis of the MOP‐R agonist d‐Ala(2),NMePhe(4),Gly‐ol(5)]enkeph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
(149 reference statements)
1
14
0
Order By: Relevance
“…Similar findings have been obtained in vitro in tissue obtained from patients with temporal lobe epilepsy [36]. It has been demonstrated that under basal conditions the uptake of glutamate from the extracellular space is very rapid, however when uptake transport is inhibited by tPDC then changes in glutamate release can be unmasked [28]. Collectively, these results indicate that depolarization-dependent release of glutamate is enhanced as a consequence of seizure kindling with cocaine.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings have been obtained in vitro in tissue obtained from patients with temporal lobe epilepsy [36]. It has been demonstrated that under basal conditions the uptake of glutamate from the extracellular space is very rapid, however when uptake transport is inhibited by tPDC then changes in glutamate release can be unmasked [28]. Collectively, these results indicate that depolarization-dependent release of glutamate is enhanced as a consequence of seizure kindling with cocaine.…”
Section: Discussionsupporting
confidence: 80%
“…1a). Rapid transporter-mediated uptake may mask the detection of changes in glutamate release [28], therefore a selective excitatory amino acid transporter inhibitor tPDC [26] was added to the perfusion medium for subsequent studies. tPDC caused significant (approximately fivefold) increase of glutamate levels in both kindled and control mice ( P  < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Often, increases in dialysate glutamate levels can be seen only when its uptake is blocked. Thus, in a recent paper, Schepers et al. (2008) showed that infusion of DAMGO increased glutamate concentrations in the rostral ventromedial medulla only in the presence of the selective glutamate transport inhibitor tPDC.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, intra-RVM infusion of DAMGO significantly decreased extracellular GABA concentration and increased PWL (Schepers et al, 2008b). These data suggest that EA may induce the release of endogenous endomorphin to activate μ opioid receptors in GABAnergic neurons and to suppress the release of GABA.…”
Section: Discussionmentioning
confidence: 75%